2012
DOI: 10.2341/10-326-l
|View full text |Cite
|
Sign up to set email alerts
|

Comparative In Vitro Validation of VistaProof and DIAGNOdent Pen for Occlusal Caries Detection in Permanent Teeth

Abstract: Laser/light fluorescence devices were highly reliable for occlusal caries diagnosis in permanent teeth but not superior in accuracy to visual methods. SUMMARYPurpose: Current caries diagnostic tools are neither very accurate nor very reliable for the detection of carious lesions of different depths. Thus, the development of new devices and techniques is needed. The aim of this in vitro study was to validate a newer fluorescence device, VistaProof (VP), and compare it with DIAGNOdent Pen (DP), direct visual (DV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 34 publications
4
23
1
3
Order By: Relevance
“…Seremidi et al 23 reported that LFE showed greater SP and lower SE than VE. In contrast, our results indicated that LFE exhibited lower SP and higher SE than the conventional methods.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Seremidi et al 23 reported that LFE showed greater SP and lower SE than VE. In contrast, our results indicated that LFE exhibited lower SP and higher SE than the conventional methods.…”
Section: Discussionmentioning
confidence: 97%
“…The fluorescence emitted from the tooth is converted into a numerical scale. 22 This quantitative measurement demonstrates validity that does not surpass that of VE for the detection of noncavitated carious lesions, 23 and its ability to discriminate various caries depths was moderate to very good. 24 LFE is suggested as an adjunct tool when conventional diagnostic methods (VE and RE) alone are insufficient.…”
Section: Introductionmentioning
confidence: 98%
“…A new version, the VistaCam CL-IX ® with removable head cameras, wireless and a light cure function, has just been launched. 32,33 The camera is placed on the tooth, pictures are recorded with specific software, which then reveals the caries scores. All these devices can be used specifically for diagnostics or treatment, but at this time only Soprolife ® can be used for both.…”
Section: Combination Of Camera and Fluorescence Systemsmentioning
confidence: 99%
“…16 On the other hand, the visual observation assisted by loops of 1,5X to 4,5X shows increased detection sensitivity. 17 Bitewing radiographs are a useful means of detecting interproximal caries; however, their advantage is quite limited to occlusal carious lesions, due to the overlay phenomenon. 18 Furthermore, 40-60% of the tooth's metal ions have to be lost so as the lesion becomes visible radiographically.…”
Section: Conventional Caries Diagnostic Meansmentioning
confidence: 99%
“…0.65) was relatively low (16.42). It is worth noting that in the study by Seremidi et al 17 the teeth were stored in tap water for a long time, which is likely to have an impact on the fl uorescence levels of the teeth. The study by Achilleos et al 43 revealed low sensitivity values (0.66-0.75) for DDPen, which may be attributed to the fact that the study was focused on the D1 level, where the performance of this device is reduced compared to the D3 level.…”
Section: Accuracy and Repeatability Of Ddpenmentioning
confidence: 99%